Antioxidant Potential of Tomato Extract and Moringa Leaf Extract - Finda Evita Marviana; Alpin Hidayatulloh; Tania Widiastuti; Umar Hafidz Asy'ari Hasbullah (Journal of Food and Agricultural Product, 2021)
Tomatoes have bioactive components which are a source of antioxidants that can prevent damage to the body. In addition, Moringa leaves also contain bioactive compounds such as polyphenols, flavonoids, ascorbic acid, and isothiocyanates that can increase the body's immune response and inhibit the activation of carcinogenesis. The content of bioactive compounds contained in tomatoes is lycopene, beta carotene, phenol, vitamin C, flavonoids. Tomatoes are also rich in antioxidants. While Moringa leaves are rich in bioactive compounds and antioxidants. Bioactive compounds found in Moringa leaves are phenols, flavonoids, chlorophyll, saponins, vitamin C. Tomatoes play a role in health by reducing the risk of oxidative stress, cancer, cardiovascular, diabetes, reducing hypertension, a direct modulator of vascular resistance through its action as a vasodilator. Moringa leaves also have the potential as antihyperglycemic, so they can control blood sugar, antibacterial activity, fight colds and flu, increase and facilitate breast milk production, as well as antimalarials and antioxidants.